Обернена задача для двовимірного рівняння дифузії в області з вільною межею - Іванчов, М.І.; Пабирівська, Н.В. (Український математичний журнал, 2013)
Установлены условия существования и единственности гладкого решения обратной задачи в области со свободной границей для двумерного уравнения диффузии с неизвестным зависящим от времени старшим коэффициентом. Уравнение неизвестной границы задается произведением известной функции пространственных переменных и неизвестной функции, зависящей от времени. We establish conditions for the existence and uniqueness of a smooth solution to the inverse problem for a two-dimensional diffusion equation with unknown time-dependent leading coefficient in a domain with free-boundary. The equation of unknown boundary is given in the form of the product of a known function of space variables and an unknown time-dependent function.